Hypothesis On the Positive U Curve Relationship Between Unemployment Rate and Productivity - Zhu, Ziju (International Journal of Management and Education in Human Development, 2022)
This paper mainly describes the U curve relationship between the unemployment rate and productivity: when productivity continues to rise, the unemployment rate will fall at first and then rise. When the contribution rate of technology input to productivity is less than the contribution rate of labor input to productivity, the unemployment rate will decrease with the increase in productivity, whereas when the contribution rates are in the opposite relationship, the unemployment rate will rise. When the contribution rate of technical input to productivity is equal to the contribution rate of labor input to productivity, there is an inflection point. This paper attempts to analyze and discuss the logical relationship between them with theoretical research methods. According to this hypothesis, policymakers should take corresponding measures to deal with the social problems caused by the rising unemployment rate.